Evaluation of a Health Communication Campaign to Improve Mosquito Awareness and Prevention Practices in Western Australia - Potter, Abbey; Jardine, Andrew; Morrissey, Annette; Lindsay, Michael D. A. (Frontiers in Public Health, 2019)
Fight the Bite represents the Department of Health's first attempt to actively raise awareness and improve prevention practices related to mosquitoes in Western Australia (WA). The multi-faceted campaign model involved a range of stakeholders and delivery methods over a 2 year period, achieving a recall rate of 8.2% among 2,500 survey participants. Significant regional differences were noted in campaign exposure, reflecting the variation in mosquito management issues throughout the State, and subsequent engagement by local government. Of those individuals with campaign recall, 43.8% reported an increase in awareness and 27.4% reported a change in behavior, which equated to a 1.7 and 1.2% change across the total survey population, respectively. The results of this study demonstrate that Fight the Bite has significantly improved awareness and prevention practices among those individuals who were exposed to the campaign. This was particularly promising, given the modest budget, resources, and time period over which the campaign was run prior to evaluation. This outcome means that Fight the Bite can be confidently adopted as a proven and standardized but regionally adaptable campaign approach to raising awareness about mosquito avoidance and mosquito-borne diseases by the Department of Health and its stakeholders. Future campaign aims include increasing reach through heightened and sustained promotion of Fight the Bite by both the Department and local government, as well as expanded collaboration with a range of stakeholders within the community.